Common Fixed Point Theorems for Weakly Compatible Maps Satisfying a General Contractive Condition - Cristina Di Bari; Calogero Vetro (International Journal of Mathematics and Mathematical Sciences)
We introduce a new generalized contractive condition for four mappings in the framework of metric space. We give some common fixed point results for these mappings and we deduce a fixed point result for weakly compatible mappings satisfying a contractive condition of integral type.